PROTOTYPE COMMUNITY BASED EDUCATION WAKAF DALAM ISLAM - Nurhadi, Drs. (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
This study aims at reviewing how management of Waqaf institution in the system of Islamic education which is focused on the waqaf along the history of Islamic education, waqaf institution and the autonomy of Islamic education. The author uses descriptive approach to the history of waqaf institution and Islamic education. Ultimately, the author concluded that waqaf institution should be promoted because it is one of the pillars in supporting Islamic education. This is supported by the fact that along the history of Islam waqaf has been very active in supporting Islamic education. Finally, the author also concluded that in the discourse of autonomy of education, waqaf institution should be managed together, side by side, with education institutions.